The Mexican Lottery as a Tool to Promote Visual Culture in the Editorial Design Process - Gutiérrez Cruz, Irma Lucía (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
The Mexican lottery is a classic Mexican game as an activity where the students of the Bachelor of Design in Graphic Communication at the University of Guadalajara develop and allow the reinforcement of knowledge of the editorial design process. Design a lottery with the theme, where the idea through the concept and management of the form: identifies the actors, with images of each of the processes, reinforcing the visual culture, build and share their visual references, is generated with the letters, a visual-conceptual representation of the actors and a learning that includes linguistic and verbal intelligence.